Temporal Pollution Load Index and Ecological Risks Evaluation of Some Heavy Metals in the Sediment of Elechi Creek, Port Harcourt, Nigeria - Kpikpi,P. B; Ogonodi, B. E; Davies, O. A (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Heavy metals in aquatic sediment have become public concern as a result of accumulation, bio-accumulation, bio-concentration, bio-transformation in the food web with regards to anthropogenic activities. The study was conducted to rate pollution load index and ecological risk appraisal of some heavy metals in the sediment of Elechi Creek, Port Harcourt, Nigeria. Sediment representatives were retrieved from three sites between January and December 2021. The exact levels of heavy metals (Cd, Cu, Fe, Zn, Pb and Cr) concentration were measured by atomic absorption spectrophotometer. Pollution Index models were employed, such as geo-accumulation index (I-geo), Enrichment factor (EF), and Pollution load index (PLI) were used for pollution assessment of sea bed sediment. The results demonstrate contamination factor (Cf) ranged between (0.027 mg/Kg) and Cd (0.31 mg/Kg) indicated (<3) moderate contamination, I-geo ranged between Cd (0.000213 mg/Kg) and Fe (297142.8 mg/Kg) indicated (>5) exceedingly pollution, EF ranged between Fe (96.86) and Cr (99.96) indicated (>1) enrichment, PLI ranged between Cu (0.0023 mg/Kg) and Fe (0.69 mg/Kg) indicated (0) no pollution while ERI ranged between Cr (0.12 mg/Kg) and Cd (135.97 mg/Kg) indicated (<320) high ecological risk. The study showed that (I-geo), (EF) and (ERI) have a significant high toxic level of heavy metals from illegal oil operations. The need for urgent monitoring and regulation by government agencies to protect the environment to avoid further pollution.